Bacterial Associations with Legumes - Peix, Alvaro; Ramírez-Bahena, Martha H.; Velázquez, Encarna; Bedmar, Eulogio J. (Critical reviews in plant sciences, 2015)
Legumes form a large group of plants that constitute the third largest family of angiosperms, including near 20,000 species and 750 genera. Most of them have the ability to establish symbioses with diazotrophic bacteria, collectively known as rhizobia, which induce root nodules where biological nitrogen fixation takes place, conferring legumes a relevant ecological advantage. This group of bacteria that for many years was thought to be formed by a scarce number of genera and species within alpha proteobacteria, shows nowadays an important genetic diversity including species phylogenetically divergent both in core and symbiotic genes sequences. Together with rhizobia, other endophytic bacteria are present in legume nodules coexisting with rhizobial strains and their ecological role remains unknown in most cases, but they likely have an effect in plant health, plant growth or even in the rhizobia-legume symbiosis. In this review we present an overview of the associations of bacteria with legumes, the current available knowledge on the phylogenetic diversity of both rhizobia and endophytic bacteria inhabiting root nodules, and the symbiotic features used to define symbiovars in rhizobia.